A Study of Comparison of The Physical Characteristics of Lightweight Foam Concrete Additional Selected Natural Fiber - musa, kamaruzaman; Mustafa Daldal, Ahmed Bilal Efifi (Progress in Engineering Application and Technology, 2020)
Lightweight foam concrete (LFC) has the disadvantage of being brittle and to overcome this problem, natural fibers were added to the LFC design to produce lighter and stronger concrete bonds. This study aims to identify the type of natural fiber that is suitable to be used as an additive in LFC design by comparing its characteristics in terms of compressive strength and water absorption as well as comparing natural fibrous LFC with LFC without standard fiber British Concrete Association (BCA). This study uses the method of analyzing the findings of previous studies and a total of five selected journals that use different types of natural fibers as additives in KRB design namely kenaf fiber, jute fiber, oil palm fiber, sisal fiber and coconut fiber that has been treated using sodium hydroxide solution ( NaOH) all of them. The potential of this fibrous LFC is studied based on a comparison of compressive strength and water absorption tests that have undergone a curing process for 28 days. The results of the study found that kenaf, palm and coconut fibers are able to increase the compressive strength of LFC compared to jut and sisal fibers. Proper fiber selection promises a longer LFC lifespan.